2010
DOI: 10.1177/0898264309358617
|View full text |Cite
|
Sign up to set email alerts
|

Who Participates? Accounting for Longitudinal Retention in the MIDUS National Study of Health and Well-Being

Abstract: Objectives-This article uses data from MIDUS (Midlife in the United States), a national study of Americans (N = 7,108), to investigate factors that predict longitudinal retention. With its extensive age range (25-75 at Time 1) and long-term design (9-to 10-year survey interval), MIDUS is useful for investigating common sociodemographic and health predictors of continuing participation.Method-The authors conducted logistic regression analyses of baseline sociodemographic and health variables predicting retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
280
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(301 citation statements)
references
References 31 publications
17
280
4
Order By: Relevance
“…UWSC staff helped design a questionnaire using the most valid rating scales and reliable research methods. The questions were tested on a sample population, and the telephone algorithm was developed by professionals in healthcare data collection [12,51]. Although we did not conduct a formal analysis on the validity of questionnaire followup, we previously conducted a similar study with patients having undergone hip arthroplasty in which we achieved a similar response rate (65%) [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UWSC staff helped design a questionnaire using the most valid rating scales and reliable research methods. The questions were tested on a sample population, and the telephone algorithm was developed by professionals in healthcare data collection [12,51]. Although we did not conduct a formal analysis on the validity of questionnaire followup, we previously conducted a similar study with patients having undergone hip arthroplasty in which we achieved a similar response rate (65%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…The University of Wisconsin Survey Center (UWSC) at the University of Wisconsin-Madison (Madison, WI, USA) was selected for their expertise in collecting health data for state and federal agencies [12,51] and having no affiliation with any of the participating centers. UWSC designed an instrument that would collect specific, unique data we sought to collect on the level of satisfaction, function, residual symptoms, ability to return to previous employment (with or without limitations), and the ability to return to the most preferred preoperative activity 1 to 4 years after TKA.…”
Section: Methodsmentioning
confidence: 99%
“…Sample retention was selective towards higher participation of whites, females, and married individuals as well as individuals with better health and more education. 13 Since no information on habitual sleep duration was obtained in the first measurement wave, only data from the second wave were analyzed in the present study. Information on insomnia symptoms was available for N=1797, valid information on sleep duration on weekdays and weekends was available for N=1755.…”
Section: Participantsmentioning
confidence: 99%
“…The longitudinal retention rate of the national RDD sample is 71 percent, adjusting for mortality of the respondents. Multivariate logit regression of attrition revealed that those who failed to respond to the second wave were more likely to be nonwhite males with low education and income level (attrition in MIDUS is thoroughly analyzed in Radler and Ryff 2010). In light of the attrition rate between waves, we employ multiply-imputed data throughout our analyses (Arbuckle 1996;Graham 2009;Peugh and Enders 2004;Rubin 1976;Schafer 2003).…”
Section: Datamentioning
confidence: 99%